STUDI KELAYAKAN USAHA TANI KOPI DAN KARAKTERISTIK RUMAH TANGGA USAHA TANI KOPI DI KABUPATEN OGAN KOMERING ULU SELATAN - Dana Megayani (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
Ogan Komering Ulu Selatan (OKUS) is one of the regencies in South Sumatera with the largest coffee plantation area. Despite the decrease in the plantation sector, the number of household coffee farmers increased by 7.63 percent, based on the Agriculture Cencus of 2013, compared to that of 2003. The question is whether the coffee farming profitable for the farmers. To describe the farmers characteristics and to analyze the economic feasibility of the coffee farming in OKUS, the study on the data obtained from the Cost-Benefit Coffee Farming Survey (SOUT) of the 2014 was carried out using descriptive and quantitative analysis of R/C Ratio. As a result, the coffee farming is profitable and feasible especially in terms of legal, social and economical aspects. However, the farmers are still weak in the technical and business management aspect, due to their traditional management practises. Demographically, the farmers are dominated by low-educated men and each household farmer manages 1,000-3,000 coffee trees with the tree age in between 8 and 15 years. The household housings are categorically as good. This study reccommends an effort of institutional empowerment and capacity building on the farmers as well as a strategy in the agriculture activity, either in the farmers, the associated companies, and the local government, in order to increase the quality of the coffee production.